A multicenter analysis of treatment patterns and clinical outcomes of subsequent therapies after progression on palbociclib in HR+/HER2− metastatic breast cancer. (June 2021) - Li, Yi; Li, Wei; Gong, Chengcheng; Zheng, Yabin; Ouyang, Quchang; Xie, Ning; Qu, Qing; Ge, Rui; Wang, Biyun
Introduction: Endocrine therapy and cyclin-dependent kinase (CDK) 4/6 inhibitors (CDK4/6i) are standard treatment options for hormone receptor positive (HR+)/human epidermal growth factor receptor 2 negative (HER2–) metastatic breast cancer (MBC). However, the efficacy of standard subsequent therapies after CDK4/6i-based treatment is unclear. This study aimed to examine physician practice patterns and treatment outcomes of subsequent therapies administered after progression on palbociclib therapy in clinical practice. Methods: The study included 200 patients with HR+/HER2– MBC who underwent subsequent treatments after progressing on palbociclib-based regimens in five Chinese institutions between August 2017 and April 2020. The treatment pattern, progression-free survival (PFS), overall survival (OS), and objective response rate (ORR) were reported. Results: A total of 200 patients were included, of whom 147 (73.5%) and 53 (26.5%) received subsequent chemotherapy and endocrine therapy, respectively. The frequently used monochemotherapy regimens were taxane ( n = 29), capecitabine ( n = 21), and vinorelbine ( n = 17), while the endocrine therapy regimens were chidamide plus exemestane ( n = 16) and everolimus plus exemestane ( n = 9). The overall median PFS (mPFS) was 5.5 months, with no significant difference in mPFS between the chemotherapy and endocrine therapy groups ( p = 0.669). However, among patients not sensitive to prior palbociclib treatment, those administered chemotherapy had significantly longer PFS than those administered endocrine therapy ( p = 0.006). The mPFS with endocrine therapy after first-, second-, and subsequent-line palbociclib was 13.4, 3.1, and 4.1 months, respectively ( p = 0.233); in contrast, the mPFS with chemotherapy was 7.2, 6.5, and 4.9 months after first-, second-, and subsequent-line palbociclib, respectively ( p = 0.364). The median OS was not achieved. The ORR was 10.6% among the 198 patients included in the analysis. Conclusions: Physicians prefer chemotherapy over endocrine therapy for the treatment of patients with HR+/HER2– MBC who develop progression on palbociclib. Sensitivity to previous palbociclib treatment might be one of the indicators for predicting response to subsequent treatment. ClinicalTrials.gov identifier: NCT04517318